Socio-economic determinants of attendance at diabetes self-management education program: using Andersen's behavioral model - Javad Javan-Noughabi; Seyed Saeed Tabatabaee; Sajad Vahedi; Tahere Sharifi (BMC, 2022)
Abstract Background Diabetes self-management education is an effective factor for improving outcomes and quality of life in patients with diabetes. However, little information is available on the factors associated with participation or non-participation in self-management education programs in people with diabetes. The aim of this study was to explore the factors affecting on the attendance of patients with diabetes in the diabetes self-management education program. Methods A cross-sectional study was conducted in 2019 on 384 patients with diabetes referred to the main comprehensive health centers of Mashhad, Iran. All patients were linked with a diabetes self-management education program that lasted three months and involved 12 sessions. We explore the factors affecting on attending in diabetes self-management education program using Andersen's behavioral model. Data for independent variables (predisposing, enabling, and need factors) were gathered at the beginning of the training program using registration forms. Dependent variable (attendance of patients with diabetes in the training program) was checked at the end of the program. Univariate and multivariate analysis were done with SPSS v.25. Results The results of this study showed that women were less likely to participate in the self-management education program than men (OR=0.414; P<0.05). Also, age, travel time, health status and years with diabetes have negative significantly correlated with participation in the education program (P<0.05). The study showed that patients with diabetes aged≥65 were less participated in the training program than those ≤40 (OR=0.159; P<0.05). Also, patients who lived farther than 40 min away from training center were less likely to participate for this program than patients that live in an area<20 min away from training center (OR=0.196; P<0.05). Odds of attending in training program for patients with poor health status was less than patients with excellent health status (OR=0.282; P<0.05). Participation in training program were low in patients with more than 5-year diabetes duration compared to less than 1 year (OR=0.176; P<0.05). Conclusion The implementation of the classes at the right time and online, Reduce the distance between people and the place of the class, providing facilities and providing infrastructure may be appropriate to involve women and the elderly.